Growth & Development of Indian Sub-Continent Seaports – A Strategic Container Transshipment Perspective - Sricharan, K. (Management Today, 2018)
A strategically located seaport contributes immensely to the overall economic development of the region. This paper studies the Indian Sub-Continent container sea borne trade and attempts to find the factors contributing to the growth and development of container hub seaports in the region. The ports of Colombo, Vallarpadam, Vizhinjam and Enayam are compared in terms of potentiality, implication and benefits. Transshipment port identification, development and selection involves a huge variety of decisions based on complex information, cognitive and social constraints. These decisions impact the economy of the nation and the regions involved. The factors that influence these decisions and ultimately operational processes are an intriguing field of study and an attempt is made to discuss their influence in the development and growth of the four ports considered in this paper. The study is visualized to provide information to all stake holders involved in the port development decision making process and to highlight the overall impact to the sub – continent.